Determination of Competencies Needed in Patternmaking by Clothing and Textile Students for Large-Scale Garment Production in Anambra State - Angela, Adilo Obioma (BOHR International Journal of Advances in Management Research, 2022)
This study looked into competencies needed in patternmaking by clothing and textile students for largescale garment production in Anambra State. Based on a descriptive survey research methodology, the study was guided by three research questions and three hypotheses that were significant at the level of 0.05. To concentrate on a determined specialized number, purposive sampling was used as the sampling approach. Twenty-five Home Economics Education students constituted the sample size for the study. Data were collected using a questionnaire produced by the researcher. Two professionals independently validated the instrument. Cronbach’s alpha was employed to examine the internal consistency of the instrument, and reliability value of 0.79 was obtained. A ttest was used to evaluate the hypotheses after the responses were analyzed using the arithmetic mean and standard deviation scores. The results showed that there is no significant difference in the mean ratings of state and federal college of education students in sloper/block patternmaking, flat pattern drafting and fashion draping for largescale garment production in Anambra State. Recommendations and conclusions were drawn based on the findings.